Waiting times for elective orthopaedic surgeries in a teaching hospital and their influencing factors - Sharifa Ezat WP; Azimatun NA; Nik Jasmin NM; Syed Aljunid (Penerbit UKM, 2009)
Long waiting time for elective operations is a usable key performance index of ineffi-ciency in services. A cross-sectional study for orthopedic elective surgery waiting times and their influencing factors was done in a teaching hospital, from January 2003 to June 2004; using case-mix patient’s coded records. Main outcomes measured were length of waiting time from first seen at the specialist clinic until surgery (T1) and length of waiting time from the time date of surgery was given until surgery (T2). The median waiting time for T1 was 23 weeks (5.75 months) and 5.86 weeks (1.47 months) for T2. Chi square test was significant for T1 which includes age, comorbidity but only ethnicity was significant for T2. However, multiple logistic regression showed patients paid by third party (OR) of 1.97 (95%CI:1.05-3.72) were significantly likely to wait longer than those who paid out of their own pocket. For T2, women (OR) of 2.29 (95%CI: 1.19-4.42), Indian (OR) of 2.50 (95%CI: 1.16-5.38) and who are self employed (OR) of 4.28 (95%CI: 1.23-14.97) were significantly more likely to have shorter waiting time. Thus predictors for overall waiting time are age, comorbidity, ethnicity, occupa-tion and the method of paying for services rendered by the patients.